Infrared measurements of column amounts of stratospheric constituents in the Antarctic winter, 1987 - Coffey, M. T.; Mankin, William G. (1988)
The discovery of Farman et al. of recent large depletions of ozone in the Antarctic stratosphere in the austral spring has aroused great interest because of its serious potential consequences, as well as its surprising nature. An airborne expedition, including 21 experiments on two aircraft, was mounted for Punta Arenas, Chile, in August and September, 1987, to gather a wide range of data to understand the origins and implications of this phenomenon, known as the ozone hole. As a part of this expedition, a high resolution Fourier transform spectrometer was flown on the DC-8, measuring the column amount of a number of trace gases above the flight altitude. Column results are presented only from the flight of September 21; results from other flights are included in an accompanying paper. The deduced column for ozone HCl, and NO2 deduced from the spectra, plotted as a function of latitude are shown. It should be noted that there are many other factors varying as well as the latitude, but latitude seems to be the variable which most clearly provides a passage across the vortex boundary. It can be seen that south 76 degrees S., the column of ozone, HCl, and NO2, all decreas markedly, The ratio of HCl to Hf, normally about 5:1 in midlatitudes, approaches unity. Clearly the chemistry of chlorine and nitrogen are disturbed in the region of low ozone. While dynamical theories could perhaps explain a reduction of these three gases in the same region, since all are of stratospheric origin, it is difficult to see how any purely dynamical mechanism could produce the observed HCl:HF ratio, since the two gases have similar origins. A close look at other species to be reported as well as the correlation with other measurements, such as ClO supports the conclusion that the ozone depletion is a result of chemical processes which deplete HCl and NOx relative to the midlatitude situation.